Synaptic and nonsynaptic mitochondria demonstrate a different degree of calcium-induced mitochondrial dysfunction - Yarana C. (2014)
Aims: Since variety in response to Ca 2+-induced mitochondrial dysfunction in different neuronal mitochondrial populations is associated with the pathogenesis of several neurological diseases, we investigated the effects of Ca 2+ overload on synaptic (SM) and nonsynaptic mitochondrial (NM) dysfunction and probed the effects of cyclosporin A (CsA), 4′- chlorodiazepam (CDP) and Ru360 on relieving mitochondrial damage. Main methods: SM and NM mitochondria were isolated from rats' brains (n = 5/group) and treated with various concentrations (5, 10, 100, and 200 μM) of Ca 2+, with and without CsA (mPTP blocker), CDP (PBR/TSPO blocker) and Ru360 (MCU blocker) pretreatments. Mitochondrial function was determined by mitochondrial swelling, ROS production and mitochondrial membrane potential changes (ΔΨm). Key findings: At 200-μM Ca 2+, SM presented mitochondrial swelling to a greater extent than NM. At 100 and 200-μM Ca 2+, the ROS production of SM was higher than that of NM and ΔΨm dissipation of SM was also larger. CsA, CDP and Ru360 could reduce ROS production of SM and NM with exposure to 200-μM Ca 2+. However, only Ru360 could completely inhibit ROS generation in both SM and NM, whereas CsA and CDP could only partially reduce the ROS level in SM. Moreover, CsA and CDP pretreatments were not able to restore ΔΨm. However, Ru360 pretreatment could protect ΔΨm dissipation in both SM and NM, with complete protection observed only in NM. Significance: Our findings suggested that mitochondrial calcium uniporter is a possible major pathway for calcium uptake in both mitochondrial populations. However, SM might have additional pathways involved in the calcium uptake. © 2012 Elsevier Inc.